Statistical Systems in English and Uzbek Morphology (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the statistical systems of morphology in English and Uzbek, with a focus on the distribution and frequency of morphemes, the role of affixation, and the differences in word formation processes between these two languages. English, an analytic language, relies on a relatively simple system of affixation and word order to convey grammatical meaning. In contrast, Uzbek, an agglutinative language, uses an extensive system of suffixes to form complex words, allowing for more compact expressions of meaning. By analyzing corpus data, this paper examines how morphological elements in both languages are used and how they contribute to sentence structure and meaning. The comparison provides insights into the linguistic typology of English and Uzbek and has practical implications for language learning, translation, and computational linguistics